RETRACTED ARTICLE: Lupeol induces apoptosis and inhibits invasion in gallbladder carcinoma GBC-SD cells by suppression of EGFR/MMP-9 signaling pathway - Liu, Yan (Cytotechnology, 2014)
The cytostatic drug from fruits and other plant derived products have acted as a chemotherapeutic agent used in treatment of a wide variety of cancers. Lupeol, a dietary triterpene, present in many fruits and medicinal plants, has been shown to possess many pharmacological properties including anti-cancer effect in both in vitro and in vivo assay systems. However, the cancer proliferative and invasive inhibitory effects and molecular mechanisms on gallbladder carcinoma GBC-SD cells have not been studied. In the present study, GBC-SD cells were treated by lupeol and subjected to methyl thiazolyl tetrazolium analysis, Hoechst 33342 staining, annexin V/propidium iodide double-staining, transwell chamber assay and Western blot analysis. In addition, GBC-SD xenograft tumors were established in male nude BALB/c mice, and lupeol was intravenously administered to evaluate the anti-cancer capacity in vivo. Our results showed that lupeol inhibited the proliferation, migration, invasion and induced apoptosis of GBC-SD cells in a dose-dependent manner in vitro. Furthermore, the expression of p-EGFR, p-AKT and MMP-9 levels were significantly down-regulated. These protein interactions may play a pivotal role in the regulation of apoptosis and invasion. More importantly, our in vivo studies showed that administration of lupeol decreased tumor growth in a dose-dependent manner. Immunohistochemistry analysis demonstrated the down-regulation of p-EGFR and MMP-9 in tumor tissues following lupeol treatment, consistent with the in vitro results. Taken together, our findings indicated that lupeol can induce apoptotic cell death and inhibit the migration as well as invasion of GBC-SD cells. The mechanism may be associated with the suppression of EGFR/MMP-9 signaling. These results might offer a therapeutic potential advantage for human gallbladder carcinoma chemoprevention or chemotherapy.